2015
DOI: 10.3164/jcbn.15-75
|View full text |Cite
|
Sign up to set email alerts
|

Sodium 4-phenylbutyrate prevents murine dietary steatohepatitis caused by <i>trans</i>-fatty acid plus fructose

Abstract: Excess consumption of trans-fatty acid could increase the risk of non-alcoholic steatohepatitis (NASH); however, treatment targeting trans-fatty acid-induced NASH has not been examined. Here we focused on the influence of trans-fatty acid intake on endoplasmic reticulum (ER) stress in hepatocytes, so we investigated the effect of the chemical chaperone 4-phenylbutyric acid (PBA), on trans-fatty acid-caused steatohepatitis using diabetic KK-Ay mice. Elaidic acid (EA, trans-fatty acid) alone did not cause defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Previously, Koppe and colleagues showed that compared to diets high in saturated fatty acids, a diet high in industrial trans fatty acids markedly increased plasma ALT activity in AKR/J mice, suggesting enhanced liver damage . Furthermore, studies in different mouse strains revealed that diets rich in industrial trans fatty acids promote hepatic steatosis and fibrosis . Our in vivo study, which provides the most detailed characterization of the effects of industrial trans fatty acids on the liver, extends these findings by showing that a diet enriched in trans fatty acids enhances liver steatosis and fibrosis, and raises hepatic triglyceride levels, hepatic cholesterol levels, plasma acute phase proteins, and plasma ALT activity.…”
Section: Discussionsupporting
confidence: 71%
“…Previously, Koppe and colleagues showed that compared to diets high in saturated fatty acids, a diet high in industrial trans fatty acids markedly increased plasma ALT activity in AKR/J mice, suggesting enhanced liver damage . Furthermore, studies in different mouse strains revealed that diets rich in industrial trans fatty acids promote hepatic steatosis and fibrosis . Our in vivo study, which provides the most detailed characterization of the effects of industrial trans fatty acids on the liver, extends these findings by showing that a diet enriched in trans fatty acids enhances liver steatosis and fibrosis, and raises hepatic triglyceride levels, hepatic cholesterol levels, plasma acute phase proteins, and plasma ALT activity.…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that PBA may act as a histone deacetylase inhibitor, serve as a chemical chaperone, or act as an ammonia scavenger (17). Furthermore, PBA has been found to suppress endoplasmic reticulum stress and exert anti-inflammatory effects (18)(19)(20)(21). The authors of the present study have previously reported that PBA may function as a therapeutic reagent for neurodegenerative disorders, and that intraperitoneal administration of PBA suppresses the onset of experimental murine colitis (22,23).…”
Section: Introductionmentioning
confidence: 83%
“…In the present study, orally administered PBA was demonstrated to delay the onset of experimental colitis. PBA treatment is not accompanied by the particular side effects of existing IBD therapeutics, and has the added benefit of an oral route of administration (15)(16)(17)(18)(19)(20)(21). PBA may therefore be one of a new type of therapeutic agents, which includes anti-TNF-α therapies (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…For histological evaluation, liver tissues were fixed in 10% buffered formalin and embedded in paraffin, and hematoxylin–eosin staining was carried out. Caspase cleavage product of cytokeratin (ccCK) 18 was detected by immunohistochemistry using M30 CytoDEATH monoclonal antibody (Roche, Basel, Switzerland) as described previously . Briefly, deparaffinized tissue sections were incubated with a monoclonal anti‐M30 antibody and secondary biotinylated anti‐mouse immunoglobulin G, and the specific binding was visualized with avidin–biotin complex solution followed by incubation with a 3, 3‐diaminobenzidine tetrahydrochloride solution using a Vectastain Elite ABC kit (Vector Laboratories, Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%